PENELITIAN ANALISIS PENGUKURAN DAN PERBAIKAN WAREHOUSE PERFORMANCE PADA DISTRIBUTION CENTER DI PT. X - Singgih Singgih; Amelia Santoso; Markus Hartono (Perpustakaan Universitas Surabaya, 2018)
X Company is a company engaged in retail sector, has more than 20 distribution center which supply throughout Indonesia. There are six main activities in the distribution center, i.e., receiving, putaway, storage, order picking, issuing and return. Distribution center has important role to supply the goods to the retail stores and because of the important role. Performance measurement in distribution center needs to be developed by considering the activities in the distribution center to make a more detailed and thorough evaluation. Based on the result of the performance measurement in X Company distribution center from January 2016 to June 2016, found the average performance of 2,518 in the range 4 that considered good, but there are indicators that have lower value, gap analysis and IPA (importance-performance analysis) is used to determine the priority for performance measurement improvement and priority proposals are made with the help of HOQ (House of Quality) to obtain the proposed improvement priorities.